He hua rānei tō te kapa haka : kapa haka as a retention tool for Māori students in mainstream secondary schools : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy (Humanities and Sciences) at Massey University, Turitea, Palmerston North, New Zealand - Kerehoma, Leanne (Massey University, 2017)
Kapa Haka provides leadership opportunities and promotes awareness to the intrinsic link to culture, Māori identity, and whanaungatanga. This research attempts to identify factors within Kapa haka, which contribute to Māori students successfully participating, achieving and staying longer in school, and to highlight the benefits and value of Kapa haka for a young focus group of participants who currently reside in the Manawatū region. The focus group consists of six Māori female participants who graduated from a mainstream school, who participated and engaged in Kapa haka, who also chose to continue their schooling in post-compulsory senior secondary school years, (year11-13) and of those participants, five attended a mainstream secondary school in the Manawatū (Palmerston North) region and one other from Te Tairāwhiti (East Coast), specifically Tūranga (Gisborne). Essentially, this study demonstrates how Kapa haka and aspects within Kapa haka could be utilised as a tool to retain Māori students in secondary school and more importantly, how it contributes to their academic success whilst at the same time producing confident, outgoing and humble individuals who are doing well in their lives and, contributing to Te Ao Māori.
Keywords: Maori (New Zealand people); Education (Secondary); Folk dancing, Maori; Social aspects; High school attendance; High school dropouts; Prevention; New Zealand; Kapa haka; Kura tuarua; Whanaungatanga; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education